Cognitive reserve in multiple sclerosis: Protective effects of education. (September 2015) - Martins Da Silva, Ana; Cavaco, Sara; Moreira, Inês; Bettencourt, Andreia; Santos, Ernestina; Pinto, Cláudia; Gonçalves, Alexandra; Coutinho, Ester; Samões, Raquel; Dias, Cláudia C; Teixeira-Pinto, Armando; Da Silva, Berta Martins; et al.
Background: Recent data suggest that cognitive reserve modulates the adverse effects of multiple sclerosis (MS) pathology on cognitive functioning; however, the protective effects of education in MS are still unclear. Objective: To explore education as an indicator of cognitive reserve, while controlling for demographic, clinical and genetic features. Methods: A total of 419 MS patients and 159 healthy comparison (HC) subjects underwent a comprehensive neuropsychological (NP) assessment, and answered the Hospital Anxiety and Depression Scale. Based on the HC data, MS patients' NP scores were adjusted for sex, age and education; and the estimated 5 th percentile (or 95 th percentile, when appropriate) was used to identify any deficits. Patients also performed the Mini-Mental State Examination (MMSE); and their human leucocyte antigen HLA-DRB1 and apolipoprotein E ( ApoE) genotypes were investigated. Results: Patients with higher education were less likely ( p < 0.05) to have cognitive deficits than those with lower education, even when controlling for other covariates. Other significant predictors of cognitive deficit were: age, Expanded Disability Status Scale (EDSS), Multiple Sclerosis Severity Scale (MSSS), and a progressive course. No significant association was found with the HLA-DRB1*15:01 or ApoE ε4 alleles. Conclusions: These results provide support to the use of education as a proxy of cognitive reserve in MS and stress the need to take into account education when approaching cognition in MS.